Primary Tumor Location as a Prognostic and Predictive Marker in Metastatic Colorectal Cancer (mCRC) - Bahl, Ankur; Talwar, Vineet; Sirohi, Bhawna; Mehta, Prashant; Arya, Devavrat; Shrivastava, Gunjan; Dahiya, Akhil; Pavithran, K. (Frontiers in Oncology, 2020)
Clinico-pathological differences between adenocarcinoma in the right and left colo-rectum play a role in determining the prognosis and response to treatment. Studies suggest that primary tumor location is more relevant as the disease progresses and reflects a possible difference in biology and response to therapy. This review aims to explore the clinico-pathological features of right and left colo-rectum and the impact of primary tumor location on prognosis of CRC as well as discuss the available clinical data on tumor sidedness in metastatic colorectal cancer. In so far as the clinical data of tumor sidedness is concerned, very few reviews have discussed the clinical implications of sidedness in heavily pre-treated metastatic colorectal cancer (second and subsequent lines of therapy in metastatic disease). This review aims to fill the current gap in this setting. Keywords: Adenocarcinoma, Panitumumab, Cetuximab, Bevacizumab, Colorectal cancer (CRC), Tumor sidedness, Primary tumor location, Anti-EGFR mAb